Empowerment in the Holy Qur’an: An Analysis of the Cosmic Verses in the Qur’an - Obaid, Israa Rabie (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Empowerment is one of the universal Sunnahs emphasized in the Holy Qur’an, encompassing both individual and collective dimensions. While divine empowerment is granted to both believers and non-believers, its purpose differs—serving as a reward for the former and a lure for the latter. Despite its significance, the concept of empowerment in Qur’anic discourse remains underexplored, especially in its integration of spiritual and socio-political aspects. This study aims to investigate the multidimensional nature of empowerment in the Qur’an, elucidating its conceptual foundations and categorizing its types. The research employs a qualitative descriptive-analytical method, relying on thematic exegesis (tafsīr mawdū‘ī) and content analysis of selected Qur’anic verses. The study is organized into an introduction and two main sections: the first discusses the concept of empowerment in light of Qur’anic terminology, and the second analyzes its various types and implications. Findings reveal that Qur’anic empowerment transcends political or social authority, integrating spiritual, epistemological, and ontological dimensions. It is closely tied to the believers’ role as vicegerents (khulafā’) on earth, guiding them to align faith, knowledge, and action with divine purpose. Furthermore, empowerment is portrayed as a process grounded in reflection upon cosmic signs, fostering a consciousness that blends moral integrity with practical capability. The study concludes that the Qur’anic vision of empowerment promotes a balanced framework in which ethical responsibility and societal influence are mutually reinforcing. This research contributes to the growing field of Qur’anic studies by offering a comprehensive model for understanding empowerment that bridges theology, ethics, and social leadership.